Development of a Digital Based Sit and Reach Test and Measurement Tool - Abdi Korintinus Simangungsong; Nurkadri; Sabaruddin Yunis Bangun (UNIB Press, 2023)
The purpose of this study was to produce an effective and efficient digital-based sit and reach measurement test kit as a test development and measurement of back muscle flexibility. The type of research in this research is a mixed methods research with a Research & Development (R&D) research design from Borg and Gall. This research was conducted with 9 research stages namely, (1) Research and information collecting, (2) Planning, (3) Develop preliminary form of product, (4) Preliminary field testing, (5) Main product revision, (6) Main field testing, (7) Operational product revision, (8) Operational field testing, (9) Final product revision. The population in this study used students from the Faculty of Sports Science and Athletes of Pelatda Sumut. Furthermore, from the Phase I trial, totaling 15 people showed a score of 87.8% with the Eligible criteria, then from the Phase II trial, which totaled 30 Pelatda Sumut athletes, it showed a figure of 90% in the Very Eligible category. From the results of the research/feasibility test carried out by test and measurement experts, IT experts and sports academic experts, it shows a score of 96% in the Very Eligible category, so it can be used. Based on the data obtained, the development of a digital-based sit and reach test and measurement tool was declared feasible to be developed as a test tool and measurement of back muscle flexibility.